Molecular diagnosis of cerebral toxoplasmosis: comparing markers that determine Toxoplasma gondii by PCR in peripheral blood from HIV-infected patients - Rafael Tonini Mesquita; José Ernesto Vidal; Vera Lucia Pereira-Chioccola (Brazilian Journal of Infectious Diseases, 2010)
As cerebral toxoplasmosis is the most common cerebral focal lesion in AIDS patients, this study evaluated three PCR markers for diagnosis, since some limitations remain present, such as low parasite levels in some clinical samples. The molecular markers were B22-B23 and Tg1-Tg2 (based on the B1 gene) and Tox4-Tox5 (non-coding fragment, repeated 200-300-fold). DNA samples from 102 AIDS patients with previously known diagnosis were analyzed. The cerebral toxoplasmosis group was constituted of DNA extracted from the blood of 66 AIDS patients, which was collected before or until the third day of the therapy for toxoplasmosis. DNA from the blood of 36 AIDS patients with other neurologic opportunistic infections was used as control group. Sensitivities of B22-B23, Tg1-Tg2, and Tox4-Tox5 markers were of 95.5%, 93.9%, and 89.3%, respectively. In the control group, the specificities were of 97.2% (B22-B23), 88.9% (Tg1-Tg2), and 91.7% (Tox4-Tox5). The association of at least two markers increased the PCR sensitivity and specificity. The concordance index between two markers varied from 83.3% to 93.1%. These data demonstrated that all markers evaluated here were highly sensitive for T. gondii determination, although B22-B23 has been shown to be the best. The association of two markers increases PCR sensitivity, but the procedure was more expensive and time-consuming. Keywords: AIDS, cerebral toxoplasmosis, molecular diagnosis, PCR markers